Social Isolation, Health Dynamics, and Mortality: Evidence across 21 European Countries - Yarine Fawaz; Pedro Mira (Institute of Labor Economics (IZA), 2022)
We provide a comprehensive picture of the health effects of social isolation using longitudinal data over 21 European countries (SHARE). First, using Cox regressions, we find a significant, strong and robust association between our social isolation index and mortality, which is much stronger in Eastern countries. While all of our pooled countries estimates ranged between a 20 to 30% increase in the mortality hazard for the socially isolated, that number jumps to 45% for the Eastern countries. We then estimate linear regressions to study the dynamic "value added" effects of SI on health and other mediator outcomes, and find that social isolation at baseline leads to worsening health in the next waves along all the dimensions we observe. Up to 13 percent of the effect of baseline social isolation on mortality can be imputed to the combined one-wave-ahead impact of social isolation on increased frailty, reduced cognitive function and increased smoking.
Keywords: I10; C41; 330; social isolation; loneliness; health; mortality; SHARE